Formulasi Dan Uji Fisikokimia Gel Sleeping Mask Ekstrak Kulit Buah Naga Merah Dengan Variasi Gelling Agent Hydroxypropyl Methly Cellulose (HPMC) - Ridha Dwi Aulya; Nur Ermawati (Jurnal Medika Nusantara, 2023)
Gels are semi-solid preparations formed from suspensions made up of large organic molecules and small inorganic particles that permeate the liquid. Sleeping mask It is a skin care product that is used at night (before going to bed). Serious research on natural ingredients is currently being carried out, including research in the field of cosmetics. Among the advantages of natural ingredients is their antioxidant properties, which can disrupt free radicals and cause the use of antioxidants in preventing premature aging. Dragon fruit skin contains compounds polyphenol, anthocyanins and betacyanins which have antioxidant activity. This study aims to determine the effect of the gelling agent Hydroxypropyl Methylcellulose (HPMC) on the physical properties of gel preparations sleeping mask red dragon fruit skin extract. This study uses an experimental method. Red dragon fruit skin is extracted by maceration in 96% ethanol. This study used 3 gel formulations, with various concentrations of HPMC 5%, 7% and 9%. Physicochemical tests carried out included organoleptic tests, homogeneity, pH, spreadability, adhesion, irritation and viscosity. The results of the research show the use of variations gelling agent HPMC meets the criteria for the physicochemical test of gel preparations sleeping mask from dragon fruit skin extract which produces the best formula from gel preparations sleeping mask namely formulation III (9%) has the best evaluation.